The Role of Women’s Empowerment Programs in Reducing Gender-Based - Wafiq , Alifa; Haq, Nurul (Generasi Sains Indonesia, 2025)
This paper critically analyzes how the women empowerment programs can help in reducing gender-based violence (GBV). It argues based on the insights of other disciplines that there is a transformational effect of empowerment efforts on social norms and the agency of women that is the result of education, economic participation, leadership training, and community involvement. Such programs equip women with the skills and resources to be resistant to violence and at the same time instigate a wider cultural and institutional change that challenges the patriarchal systems. The study also highlights the importance of circumstances of determinants, such as cultural acceptance, political will and integration of policies that significantly influence the effectiveness of programs. Although there are still numerous obstacles including scarce resources, set stereotypes, lack of sustainability, etc, empirical results indicate that the programs of empowerment continue to be one of the most promising ways to tackle GBV. Therefore, the article reflects the idea of multi-sectoral partnership, comprehensive program development, and long-term investment to achieve long-lasting changes in gender equality and violence elimination.